Investigation of Benthic Macroinvertebrate Fauna and Water Quality of Animal Drinking Water Troughs by Multivariate Statistical Methods: The Case of Şarkışla - Menekşe Taş Divrik (Aquatic Sciences and Engineering)
This study was conducted in 2022 to investigate the water quality and benthic macroinvertebrate fauna of water troughs in Şarkışla, a district in the city of Sivas. Fifteen stations were selected from the most used water troughs in the district and sampling was carried out in the spring, summer, and autumn seasons during peak agricultural activities. As a result, a total of 17 taxa were identified: 4 taxa belonging to Oligochaeta, 6 species belonging to Chironomidae, 2 taxa belonging to Amphipoda, and one each belonging to Gastropoda, Hemiptera, Coleoptera, Ostracoda and Trichoptera larvae. All taxa identified are new records for the study area. In addition to benthic sampling, some physicochemical parameters of water (water temperature, pH, electrical conductivity, dissolved oxygen, total hardness, calcium, magnesium, chloride, salinity, total dissolved solids, phosphate, sulphate, nitrate nitrogen, nitrite nitrogen) were also analyzed. The similarity of the stations in terms of physicochemical parameters was analyzed by utilizing the BrayCurtis similarity analysis. Accordingly, stations 2 and 4 were found to be the most similar, by 96.91%, and stations 3 and 13 were found to be the most different, by 66.46%. In addition, the relationship between the investigated physicochemical parameters was analyzed using the Pearson and Spearman Correlation Analysis. The relationship between the species and physicochemical parameters was revealed using the CCA Analysis.